Assistance and Development of Website Profile in Curug Sangereng Village - Nabila Husna Shabrina; Gideon K.F.H. Hutapea; Irmawati; Monica Pratiwi; Ardiles Akyuwen; Aditya Satyagraha; Imamul Masyhudi; Suwito Casande; Kanza Amanda (I-Com: Indonesian Community Journal, 2023)
Curug Sangereng Village, located in the independent city of Gading Serpong, Tangerang Regency, boasts a range of complete infrastructure, including offices, health facilities, educational institutions, places of worship, shopping places, and family recreation areas. However, the village presently lacks a comprehensive village profile that can serve as a means of socializing and disseminating information to its community. The objective of this community service activity, therefore, is to develop a website profile for Curug Sangereng Village that will provide information on the village's profile, public services, MSMEs, facilities, routine activities, and news about important events. In addition to developing the website, the activity will also implement a website usage assistance program to introduce and promote the use of the developed website. The assistance and development of the website for Curug Sangereng Village are part of the community service activities undertaken by Universitas Multimedia Nusantara.